Comparative study of the legal regulation of international cooperation in the field of criminal justice in the Eurasian space - Sidorova, N.V.; Serikbayev, A.M. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of this study is a comparative legal analysis of international legal and domestic norms governing international cooperation in criminal proceedings in the Eurasian space, identify gaps and conflicts, formulating proposals for the harmonization and unification of the legal foundations of cooperation. The methodological basis of this work was a systematic approach to comparative analysis, reflecting the state of legal regulation of international cooperation in criminal proceedings at the international and domestic levels, combined with a theoretical and legal study of the identified problems. In a separate direction, the authors extracted the “unique” norms of the criminal procedure codes of the states of the region, substantiating their progressiveness and formulating proposals for their extrapolation into international treaty norms and the domestic law of states. The study led to the conclusion about the heterogeneity of the legal regulation of international cooperation in criminal proceedings and the multi-level implementation of international norms. The main results of the study are the identification of existing gaps and conflicts, the formulation of clear proposals for their elimination, as well as for the improvement of existing legal norms. The main conclusion that the authors formulated in the process of working on the topic is the actualization of the revision of international treaties governing cooperation in the field of criminal proceedings (legal assistance in criminal cases), their innovation and further implementation in the domestic law of the states of the Eurasian region.